KETERLIBATAN PEMERINTAH DESA DALAM PENGELOLAAN BUMDES DI DESA TOLITEHUYU KECAMATAN MONANO KABUPATEN GORONTALO UTARA - Hariyanti; Gobel, Lisda Van; Talalu, Moh Abubakar (STISIPOL Mujahidin Buol, 2023)
This research aims to obtain an overview of how the Village Government is involved in managing Bumdes in Tolitehuyu Village, Monano District, North Gorontalo Regency. This research was carried out in Tolitehuyu Village, Monano District, North Gorontalo Regency. type of qualitative research carried out in the field, the informants in this research consisted of: a). Village Head Village officials 1 person, b). Head of Bumdes Group 1 person, c). BUMDES members 2 people, d). Society of 2 people. data collection process through observation, interviews, and documentation. The results of the research show that the involvement of the Village Government in the Management of Bumdes in Tolitehuyu Village, Monano District, North Gorontalo Regency with a research focus on coordination, cooperation and supervision has not yet run optimally, which has resulted in the management of Bumdes in the field often encountering problems that cannot run optimally according to common expectations.